Psychosomatic reactions of children from migration families - Gorbaniuk, Julia (Current Problems of Psychiatry, 2011)
The research conducted in families, separated as a result of economic migration, aimed to determine a situa-tion of the child remaining in long-lasting separation with one or both parents. Seventy seven (77) children aged 3 to 17 were qualified to the research. Interviews were conducted with the children on the basis of a questionnaire designed for the purposes of the study and allowing collecting research material.. The obtained results of the study on the random sample allowed determining proportions of exoduses among mothers and fathers and the form of care which is “organized” during the absence of the parents for the children. Separation with the parents for a longer time in the very early period of the childhood is undoubtedly a very traumatic experience for the child; surviving difficult emotions of the child by the parents supports the tendency to become withdrawn or starts me-chanisms of repression [1]. The situation of the child in the migrating family is very diverse and to a large extent depends on qualities of the relationships developed in the family before separation, either at the level of marital relationship or at the parent-child level. As Danielewicz points out, they constitute in a way a basis for creating diversity of “childhood face” of the child experiencing migration of parents [2].